2014
DOI: 10.1097/gme.0b013e31829374e8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture and Chinese herbal medicine (Zhi Mu 14) on hot flushes and quality of life in postmenopausal women

Abstract: TCM AP is superior to sham AP and verum CHM in reducing menopausal symptoms, whereas verum CHM shows no significant improvements when compared with placebo CHM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 48 publications
1
36
0
2
Order By: Relevance
“…Comparing the groups in the sixth week, group B had the most improvement. In the twelfth week, there was improvement in groups B and D. However, group B showed significant improvement when compared with group D. In consistence of our study, significant decreases in all MRS scores were reported in postmenopausal women after 12 weeks of Traditional Chinese Medicine (26). Akbari reported that fenugreek and flaxseed did not influence the severity and frequency of hot flushes before eight weeks, but after eight weeks a decrease in severity and frequency was observed in subjects who used fenugreek (27).…”
Section: Discussionsupporting
confidence: 79%
“…Comparing the groups in the sixth week, group B had the most improvement. In the twelfth week, there was improvement in groups B and D. However, group B showed significant improvement when compared with group D. In consistence of our study, significant decreases in all MRS scores were reported in postmenopausal women after 12 weeks of Traditional Chinese Medicine (26). Akbari reported that fenugreek and flaxseed did not influence the severity and frequency of hot flushes before eight weeks, but after eight weeks a decrease in severity and frequency was observed in subjects who used fenugreek (27).…”
Section: Discussionsupporting
confidence: 79%
“…1 to 5 consultations within on average 26.5 weeks for the treatment of atopic dermatitis [ 17 ] or approximately 8 consultations within 24 months for migraine [ 18 ]. Compared to clinical trials with acupuncture or osteopathy, the number of treatments in Table 2 was also similar or lower [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 95%
“…This study also goes beyond previous research by including a longer post-treatment follow-up than most studies. 32,33,35 …”
Section: Discussionmentioning
confidence: 99%